Book Review:Rural People & Communities in the 21st Century:Resilience & Transformation - SaraBeth Dew (Journal of Research in Rural Education, 2013)
David L. Brown and Kai A. Schafft's Rural People and Communities in the 21st Century: Resilience and Transformation joins the voices calling in recent years for national dialogue on an inclusive and coherent rural policy. Brown and Schafft contend that rural people and communities merit consideration in a wide range of social, economic, and environmental discussions at both local and national levels. The work compiles and analyzes data on persistence and change in rural communities, particularly addressing how rural people contribute to the American economy amid the challenges of rapid urbanization, outmigration, and farming decline"forces that have sorely tested the economic flexibility and fortitude of rural regions. Brown and Schafft offer a well-informed, tightly organized, and compact analysis of the continuous transformation of rural communities, demonstrating the importance of their histories to the social, economic, and environmental forces shaping the new millennium. The authors most particularly contribute to rural sociology and national policy studies, but their work is also fundamentally relevant for a wide range of scholars interested in community development, education, and social action. Providing numerous insights into the ways rural communities perceive themselves, the work also serves as an excellent introduction to rural Americans' conceptions of their relationships to the nation at large. "